Diversity of Insect Visitors to Oil Palm Flowers in Smallholder Plantations as a Potential Resource for Environment Based Learning in Education - Samsurizal M Suleman; Manap Trianto; Syech Zainal (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: Insect visitors to oil palm flowers, an important component in the pollination process and ecosystem services, are evaluated for their diversity in this study. The research explores their potential as a resource for environment-based learning rooted in local contexts within smallholder plantations, aiming to raise awareness and support sustainable education practices in the community. Methodology: Insects were collected using sweep nets, yellow pan traps, and direct observation. Identification was conducted using a Nikon SMZ445 stereo microscope and reference to entomological keys. Data analysis was carried out descriptively, focusing on species composition and abundance. An e-pocket book was developed as a learning resource. Main Findings: The results showed a total of 50 morphospecies of insect visitors on both male and female oil palm flowers. The number of insect species visiting male flowers was higher, consisting of 38 morphospecies belonging to 21 families and 10 orders. The results of the study were developed into a local wisdom-based pocket book focused on the diversity of insect visitors to oil palm flowers in smallholder plantations. The learning resource was validated by content experts, design experts, media experts, and students, with an average score of 81.7%, indicating it is highly suitable for use in environment-based education. Novelty/Originality of this study: This study highlights insect diversity in smallholder oil palm plantations, which is rarely documented. It also links ecological data with educational applications, providing a model for utilizing local biodiversity as a teaching resource in environmental and biology education.